Translational metagenomics - Murugesan, Selvasankar; Al Khodor, Souhaila (Journal of translational medicine, 2021)
The use of omics technologies enabled researchers to assess the microbiome at various levels including composition, function, gene expression, protein expression and microbial metabolites among others. 16sRNA gene sequencing and shotgun metagenomics can be used to analyze human microbiome composition and diversity in samples collected from various body sites. [...]researchers face statistical and computational challenges related to data normalization and accurate quantification of the microbial taxa, relative gene abundance and their metabolic activities; precise phylogenetic placement of genomes in addition to the multivariate but sparse analysis of high-dimensional compositional data. To ensure the best outreach to the scientific community, the journal offers a high standard peer review process and facilitates open access to high-quality research articles. The use of omics technologies enabled researchers to assess the microbiome at various levels including composition, function, gene expression, protein expression and microbial metabolites among others. 16sRNA gene sequencing and shotgun metagenomics can be used to analyze human microbiome composition and diversity in samples collected from various body sites. [...]researchers face statistical and computational challenges related to data normalization and accurate quantification of the microbial taxa, relative gene abundance and their metabolic activities; precise phylogenetic placement of genomes in addition to the multivariate but sparse analysis of high-dimensional compositional data. To ensure the best outreach to the scientific community, the journal offers a high standard peer review process and facilitates open access to high-quality research articles.